2012
DOI: 10.1371/journal.pone.0039843
|View full text |Cite|
|
Sign up to set email alerts
|

Heritability of Asymmetry and Lateral Plate Number in the Threespine Stickleback

Abstract: The estimation of individual fitness and quality are important elements of evolutionary ecological research. Over the past six decades, there has been great interest in using fluctuating asymmetry (FA) to represent individual quality, yet, serious technical problems have hampered efforts to estimate the heritability of FA, which, in turn, has limited progress in the investigation of FA from an evolutionary perspective. Here we estimate the heritability of number of lateral plates, their FA and directional asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 54 publications
2
31
1
Order By: Relevance
“…The habitat‐related differences in plate DA may either be a by‐product of DI or give further evidence for a functional role for DA in stickleback ecology. Previous work has shown that DA in lateral plates is heritable (Loehr et al ., ) and that the populations in this study are isolated to varying degrees (Mäkinen et al ., ), leaving open the possibility that there is a genetic basis for differences in DA between populations. FA was correlated with plate morph and was therefore difficult to separate from habitat‐related trends.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The habitat‐related differences in plate DA may either be a by‐product of DI or give further evidence for a functional role for DA in stickleback ecology. Previous work has shown that DA in lateral plates is heritable (Loehr et al ., ) and that the populations in this study are isolated to varying degrees (Mäkinen et al ., ), leaving open the possibility that there is a genetic basis for differences in DA between populations. FA was correlated with plate morph and was therefore difficult to separate from habitat‐related trends.…”
Section: Discussionmentioning
confidence: 90%
“…In the context of the present study, an evolutionary basis for habitat differences in DA is possible. Recent research has found that there is a heritable component to lateral plate DA in one of the populations (fm) used in the present study, and the same right bias in lateral plates was found in lab‐reared individuals (Loehr et al ., ). DA is generally assumed to be genetically determined (Palmer, ), and selection experiments have shown that DA can respond to selection in D. melanogaster (Pélabon et al ., , ).…”
Section: Discussionmentioning
confidence: 97%
“…; Loehr et al. ). Nevertheless, our results suggest that, despite extensive gene flow, the ecological differences among habitat types (or between basins) are strong enough to either promote plastic or genetic phenotypic divergence (e.g., West‐Eberhard ) or phenotype‐specific habitat sorting (e.g., Holt and Barfield ).…”
Section: Discussionmentioning
confidence: 96%
“…Some elements are expendable and, where it occurs, armor reduction is typically adaptive, facilitating escape from invertebrate predators and/ or providing growth advantages in fresh water (Reimchen, 1992;Barrett et al, 2008Barrett et al, , 2009Marchinko, 2009;Le Rouzic et al, 2011;Leinonen et al, 2011;Lescak and von Hippel, 2011;Lescak et al, 2012). Loss of spines and lateral plates occurs primarily via genetic change (Colosimo et al, 2004;Cresko et al, 2004;Shapiro et al, 2004;Coyle et al, 2007;Chan et al, 2010), although Loehr et al (2012), while documenting heritability of plate number, demonstrated significant environmental and maternal effect influences on lateral plate expression as well. The origin of the environmental influence on plate expression is unclear, but appears not to be caused by salinity variation (McCairns and Bernatchez, 2012;Wund, unpublished).…”
Section: Morphological Plasticity In the Radiationmentioning
confidence: 99%